PENGGUNAAN RESEP SRI CAKE OLEH KARYAWAN BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2000 TENTANG RAHASIA DAGANG: Use Of Sri Cake Recipe By Employees Pursuant To Law Number 30 Of 2000 Regarding Trade Secret - Amanda Nur Berliana; Simona Bustani (AMICUS CURIAE, 2025)
The Sri Cake shop makes efforts to maintain the confidentiality of cake recipes by appealing to employees to keep the recipes used in the production process secret, but secretly these employees make and sell products that are similar to the Sri Cake shop. Whether the Sri Cake recipe can be protected by trade secrets based on Law number 30 of 2000 concerning Trade Secrets and what legal sanctions can be given to Sri Cake employees according to Law Number 30 of 2000 concerning Trade Secrets are the main issues in this thesis. The writing of this thesis is based on normative research which is an analytical description using secondary data which is analyzed qualitatively using deductive methods to draw conclusions. Based on the analysis carried out, it can be concluded that: the Sri Cake shop recipe can be protected by Law Number 30 of 2000 concerning Trade Secrets because it meets the elements of article 1 number 1. The actions of the Sri Cake shop employees have fulfilled the trade secret law so that legal sanctions can be given. namely from the civil aspect and the criminal aspect, imprisonment can be imposed.